Advances in energy system optimization: proceedings of the 2nd International Symposium on Energy System Optimization - Bertsch, Valentin; Ardone, Armin; Jaya Soo Ria, Michael Raja Suriyah; Fichtner, Wolf; Leibfried, Thomas; Heuveline, Vincent (Birkhäuser, 2020)
Part I Optimal Power Flow -- Feasibility vs. Optimality in Distributed AC OPF: A Case Study Considering ADMM and ALADIN -- Security Analysis of Embedded HVDC in Transmission Grids -- Multi-area Coordination of Security-Constrained Dynamic Optimal Power Flow in AC-DC Grids with Energy Storage -- A Domain Decomposition Approach to Solve Dynamic Optimal Power Flow Problems in Parallel -- Part II Energy System Integration -- Optimal Control of Compressor Stations in a Coupled Gas-to-Power Network -- Utilising Distributed Flexibilities in the European Transmission Grid -- Part III Managing Demand Response -- A Discussion of Mixed Integer Linear Programming Models of Thermostatic Loads in Demand Response -- Weighted Fair Queuing as a Scheduling Algorithm for Deferrable Loads in Smart Grids -- Part IV Planning and Operation of Distribution Grids -- Cost Optimal Design of Zero Emission Neighborhoods’ (ZENs) Energy System -- Efficient Operation of Modular Grid-Connected Battery Inverters for RES Integration. p.p1 {margin: 0.0px 0.0px 0.0px 0.0px; font: 10.0px Times} p.p1 {margin: 0.0px 0.0px 0.0px 0.0px; font: 12.0px Times} span.s1 {letter-spacing: 0.0px}.
Keywords: Konferenzschrift